Casting design and simulation of gating system in rotary adaptor using procast software for defect minimization. (2020) - Kumar, R.; Madhu, S.; Aravindh, K.; Jayakumar, V.; Bharathiraja, G.; Muniappan, A.
Abstract: This work gives an idea of creating gating system for investment casting with the help of fascinating advancements in the casting field. In this study, advanced techniques are utilized for creating a part named rotary adapter. This part has a complex shaped profile and needs a high surface finish with stringent dimensional tolerance. Hence investment casting has been chosen for fabricating. Unigraphics software was used for modelling the part and the gate system as per the given dimensions. Then the part is imported to the Pro-CAST software for simulation. In this work different real time parameters were given as input and the simulation was carried out. The simulation results were analysed and the defects were identified. Different gating system has been implemented for eliminating the defects. The process was repeated in the software and the efficiency was proved with defect free casting.